Electric scooters: convenient transport or ED headache?. Issue 2 (February 2022) - Barker, M.; Pepper, T.; Dua, R.; Fan, K.
Abstract: Electric scooters (e-scooters) provide a potentially attractive means of private transportation in the pandemic era, during which use of public transport is discouraged. E-scooter use has become widespread recently, and we have noticed a concomitant rise in related craniomaxillofacial injuries, often associated with alcohol consumption and lack of protective equipment. We present here the first-published UK data on electric scooter injuries which, in the post-lockdown period, included facial lacerations, mandibular and midface fractures, avulsed teeth, and cervical spine injury. We urge that forthcoming legislation make e-scooters subject to at least the same requirements in lighting, helmet wear, and sobriety as bicycles and that, in this way, their benefits can be enjoyed while reducing associated morbidity and mortality.